Crystal structure of ethyl 2′′, 3-dioxo-7′, 7a'-dihydro-1′H, 3H, 3′H-dispiro[benzo[b]thiophene-2, 6′-pyrrolo[1, 2-c]thiazole-5′, 3′′-indoline]-7′-carboxylate. (March 2015) - Savithri, M. P.; Suresh, M.; Raghunathan, R.; Raja, R.; SubbiahPandi, A.
No abstract available